Synthesis and Quantum Chemistry Study of Nitrogen-Containing Heterocyclic Ligands - Wei, Qingli; Ding, Cai-Feng; Zhang, Shu-Sheng; Liu, Nian (Asian Journal of Chemistry, 2010)
Six novel nitrogen-containing heterocyclic ligands were synthesized. The electronic structures of these ligands have been studied by using the density functional theory of quantum chemistry program package Gaussian98. All the geometry structures of these ligands have been optimized at the level of B3LYP/6-31G*. The analysis of Mulliken populations and the main composition and proportion of the frontier orbitals indicated that these nitrogen-containing heterocyclic ligands should have some capabilities to coordinate with metal ions and the active site of each ligand have been confirmed elementarily. Investigation found that the electron repelling group containing in NN´-bis(4-picolinaminde)-4,4-benzindine is in favour of increasing the electron densities of the coordination atoms.